Uptake of COVID-19 Vaccination among Healthcare Providers in Busia County in Kenya - Juliet Kilima; Everlyne Morema; Eldah Ochieng (Evidence-Based Nursing Research)
Context: The novel coronavirus was announced as a global rampant disease in March 2020. Non-pharmaceutical interventions were imposed globally to assist in controlling the spread of the disease, which had negatively impacted the wellness of individuals and contributed to a significant decline in the global economy. Through rigorous research, the world realized the development of effective and safe vaccines given emergency use authorizations. Healthcare providers are at the highest risk of COVID-19 occasioned by their nature of work.